2018
DOI: 10.1002/ca.23244
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation during the voiding phase of micturition in healthy adults: A meta‐analysis of neuroimaging studies

Abstract: Several studies have used a variety of neuroimaging techniques to measure brain activity during the voiding phase of micturition. However, there is a lack of consensus on which regions of the brain are activated during voiding. The aim of this meta-analysis is to identify the brain regions that are consistently activated during voiding in healthy adults across different studies. We searched the literature for neuroimaging studies that reported brain co-ordinates that were activated during voiding. We excluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Micturition is a complex process, involving both voluntary and involuntary control regulated by a supraspinal network [ 11 , 12 ]. Until 1996, all available evidence for supraspinal micturition control was obtained from animal studies in cats [ 37 ] or from case reports of humans with lesions in the prefrontal cortex [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Micturition is a complex process, involving both voluntary and involuntary control regulated by a supraspinal network [ 11 , 12 ]. Until 1996, all available evidence for supraspinal micturition control was obtained from animal studies in cats [ 37 ] or from case reports of humans with lesions in the prefrontal cortex [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IFG is associated with micturition control [16,17]. Activation of the PFC has been found both in people who wanted to empty but could not as well as those who could successfully void [18].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that ACC is activated during the voiding phase of micturition (Harvie et al . ) and during bladder filling (de Groat et al . ).…”
Section: Discussionmentioning
confidence: 99%